Advances in the use of non-intubated spontaneous-ventilation video-assisted thoracoscopic surgery - Huang, Kai; Zhang, Zhanjun; Hu, Teng; Qiao, Linfeng (Frontiers in Surgery, 2025)
With the advancement of Enhanced Recovery After Surgery (ERAS), minimally invasive thoracoscopic surgery has gained widespread clinical adoption owing to its reduced trauma and faster recovery compared to traditional open chest procedures. Thoracoscopic surgery has evolved from initial three-port and two-port techniques to single-port non-intubated approaches, which preserve spontaneous breathing while minimizing trauma and accelerating recovery. NIVATS represents a groundbreaking advancement in thoracic surgery and anesthesia by innovatively avoiding endotracheal intubation and mechanical ventilation, thereby challenging conventional surgical approaches. This paper reviews the research progress on the anesthesia techniques, indications, and contraindications of Non-Intubated Spontaneous-Ventilation Video-Assisted Thoracoscopic Surgery (NIVATS), discussing its advantages compared to traditional surgical methods, its application in thoracic diseases, as well as the risks and management of NIVATS.